Efektivitas Pembelajaran Ilmu Tajwid Peserta Didik Terhadap Kemampuan Membaca Al-Qur’an - Sulaiman, Husnan; Alawiyah, Tetah (STAI Al-Musaddadiyah Garut, 2024)
The effectiveness of Tajweed learning among students is a critical aspect of the educational process that deals with the rules and principles of Tajweed for correct Qur'anic recitation. Despite this, challenges remain in students' ability to read the Qur'an in alignment with Tajweed principles. At Madrasah Tsanawiyah Miftahul Ulum in Cigedug, Garut, specifically in the seventh grade, the implementation of Tajweed learning for proper Qur'anic recitation has been ongoing for the past several years. This study aims to address the research questions, thereby elucidating: (1) the effectiveness of Tajweed learning among seventh-grade students at MTs Miftahul Ulum Cigedug Garut; (2) the Qur'anic reading abilities of these students; and (3) the impact of effective Tajweed instruction on their Qur'anic reading skills. The research employs a descriptive analytical method. The findings indicate that the effectiveness of Tajweed instruction significantly enhances students' Qur'anic reading abilities in the seventh grade at MTs Miftahul Ulum Cigedug Garut. The results demonstrate that the teaching of Tajweed is not only effective but also efficient, particularly in the context of classroom activities. This is evidenced by the noticeable improvement in students' ability to recite the Qur'an accurately, adhering to the rules of Tajweed. Keywords : Effectiveness, Learning, Reading Ability